1986
DOI: 10.3758/bf03203021
|View full text |Cite
|
Sign up to set email alerts
|

Infants’ identification of three-dimensional form from transformations of linear perspective

Abstract: The ability of infants to perceive three-dimensional structure from transformations of linear perspective was investigated in two studies. Infants were habituated to the pattern oflinear perspective transformations corresponding to a particular three-dimensional object, and their relative preference for that object as compared with a different three-dimensional object was assessed both before and after habituation. The habituation displays showed the distorting shadow cast by a rotating object and therefore pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1987
1987
1996
1996

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Recently, Shaw, Roder, and Bushnell (1986) argued in regard to an earlier presentation of this study (Kellman & Short, 1985) that infants might have discriminated the two objects in this study without perceiving 3-D form, by detecting for each object the angles of intersection of its component triangles at the moment in its rotation when its projection consists of only two lines. Their argument misunderstands the design of this study, in which this particular view (or any 2-D view) of an object occurred either in habituation or in the test trials but never in both.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Recently, Shaw, Roder, and Bushnell (1986) argued in regard to an earlier presentation of this study (Kellman & Short, 1985) that infants might have discriminated the two objects in this study without perceiving 3-D form, by detecting for each object the angles of intersection of its component triangles at the moment in its rotation when its projection consists of only two lines. Their argument misunderstands the design of this study, in which this particular view (or any 2-D view) of an object occurred either in habituation or in the test trials but never in both.…”
Section: Discussionmentioning
confidence: 73%
“…Shaw and Bushnell (1983) suggested that changes in brightness and texture are necessary for early 3-D form perception. Using a shadow-casting technique, they displayed perspective tranformations of a rotating object in the absence of brightness and texture gradients.…”
Section: Experiments 3amentioning
confidence: 99%
“…Moreover, movement leads to systematic motor responses such as optokinetic nystagmus (Hainline, Lemerise, Abramov, & Turkel, 1984; Kremenitzer, Vaughan, Kurtzberg, & Dowling, 1979; McGinnis, 1930; Tauber & Koffler, 1966), pursuit tracking (Aslin, 1981; Dayton, Jones, Steele, & Rose, 1964; Kremenitzer et al, 1979; Roucoux, Culee, & Roucoux, 1983), reaching (Hofsten, 1980, 1983; Hofsten & Lindhagen, 1979), and postural control (Bertenthal & Bai, 1989; Butterworth & Hicks, 1977; Lee & Aronson, 1974). Furthermore, stimulus movement imparts important information about the properties of objects, such as relative size and distance (Granrud, 1986), shape (Kellman, 1984; Kellman, Hofsten, & Soares, 1987; Kellman & Short, 1987; Shaw, Roder, & Bushnell, 1986; Yonas, Arterberry, & Granrud, 1987), the connectedness of object components (Hofsten & Spelke, 1985; Kellman & Spelke, 1983; Kellman, Spelke, & Short, 1986; Spelke, Hofsten, & Kestenbaum, 1989), and the geometric structure of point–light displays (Bertenthal, Proffitt, Kramer, & Spetner, 1987; Fox & McDaniels, 1982). Finally, stimulus movement is ubiquitous in that spontaneous eye, head, and body movements create nearly continuous motions of the image of the visual environment across the retina.…”
Section: Mechanisms Underlying Motion Preferencesmentioning
confidence: 99%
“…In addition, the motion of objects in the environment provides kinetic optical information for their shape and motion in depth. The results of recent studies suggest that infants in the first year of life are able to perceive some aspects of three-dimensional object shape specified by kinetic information (Kellman, 1984;Kellman & Short, 1985;Owsley, 1983;Shaw, Roder, & Bushnell, 1986;Yonas, Arterberry, & Granrod, 1987). The goal of the present study was to extend this work by demonstrating that 4-month-olds can perceive the difference between two rectilinear forms specified by kinetic information in the absence of figural features such as contours and intersections.…”
mentioning
confidence: 99%